2011
DOI: 10.1007/s10461-011-9960-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Behaviors Among Female Sex Workers in Southwest China

Abstract: Despite the recognized importance of HIV testing in prevention, care and treatment, HIV testing remains low in China. Millions of female sex workers (FSW) play a critical role in China's escalating HIV epidemic. Limited data are available regarding HIV testing behavior among this at-risk population. This study, based on a cross-sectional survey of 1,022 FSW recruited from communities in Southwest China, attempted to address the literature gap. Our data revealed that 48% of FSW ever took HIV testing; older age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 33 publications
7
83
0
1
Order By: Relevance
“…This proportion is similar to the percentage reported in a 2012 national biological and behavioral survey (77.6%). 3 The percentage observed in Benin is much higher than reported elsewhere, such as in Guinea 26 and China, 30 where only 26.6% and 48% of FSWs, respectively, reported earlier HIV testing. Our study revealed a higher proportion of FSWs in Benin who had had an HIV test during the past year (65.3%) than that reported by UNAIDS and WHO in 2009.…”
Section: Discussionmentioning
confidence: 84%
“…This proportion is similar to the percentage reported in a 2012 national biological and behavioral survey (77.6%). 3 The percentage observed in Benin is much higher than reported elsewhere, such as in Guinea 26 and China, 30 where only 26.6% and 48% of FSWs, respectively, reported earlier HIV testing. Our study revealed a higher proportion of FSWs in Benin who had had an HIV test during the past year (65.3%) than that reported by UNAIDS and WHO in 2009.…”
Section: Discussionmentioning
confidence: 84%
“…The rate of HIV testing among young men (Petroll et al, 2009), injecting drug users (IDUs) (White et al, 2013), adults (Du, Camacho, Zurlo, & Lengerich, 2011) accounted for 76%, 97%, 39.9% in lifetime and 52%, 85.7%, 10.6% during the past year, respectively. Forty-eight per cent of FSWs (Hong et al, 2012) and 42% of women whose husbands were heavy drinkers (Satyanarayana, Chandra, (Medhi et al, 2012). This rate among our sample, MMTDs, is higher than among adults, but lower than that among MSM, young men, IDUs, FSWs and women.…”
Section: Risk Behaviours and Utilisation Of Recent Hiv Testing Servicementioning
confidence: 99%
“…However, many groups access testing late or do not use HIV testing services properly (Obermeyer & Osborn, 2007). Previous researches in both developed and developing countries have assessed HIV testing among different groups (Fernandez et al, 2005;Giang, 2010;Hong et al, 2012;Medhi et al, 2012;Petroll et al, 2009;Sifakis et al, 2005;Song et al, 2011;Zhang, Zhang, Gao, He, & Detels, 2012). These studies reported that HIV testing rates range from 2.3% to 92%.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of female sex workers were found to play a critical role in China's escalating HIV epidemic. Hong et al (2012) revealed in their study that among the 48% of female sex workers who ever took HIV testing, older age, less education, working in higher-income commercial sex venues and better HIV knowledge were associated with HIV testing. They further indicated that those who never took HIV testing were more likely to engage in high-risk behaviours including inconsistent condom use with clients and stable partners.…”
Section: Introductionmentioning
confidence: 97%